Impact of Postoperative Continuous Renal Replacement Therapy in Lung Transplant Recipients. Issue 6 (June 2020) - Katahira, Masato; Hirama, Takashi; Eba, Shunsuke; Suzuki, Takaya; Notsuda, Hirotsugu; Oishi, Hisashi; Matsuda, Yasushi; Sado, Tetsu; Noda, Masafumi; Sakurada, Akira; Sidhu, Aman; Okada, Yoshinori
Abstract : Background: Acute kidney injury (AKI) is a common complication after lung transplant (LTx), and continuous renal replacement therapy (CRRT) is increasingly of use to critically ill patients who have developed AKI. However, the optimal timing or threshold of kidney impairment for which to commence CRRT after LTx has been uncertain. There has also been limited information on the impact of CRRT among LTx recipients (LTRs) introduced in the early posttransplant period on survival, graft function, and renal function. We aimed to review LTRs who developed AKI requiring CRRT postoperatively and followed their long-term outcomes at Tohoku University Hospital (TUH). Methods: Medical records of consecutive patients who underwent LTx at TUH between 2000 and 2018 were reviewed, with follow-up to 2019 inclusive. Results: Although mortality in those who required CRRT (n = 21) was increased versus those who did not require CRRT (n = 85)( P = 0.024), conditional survival beyond 3-month posttransplant was not affected ( P = 0.131). Additionally, the cumulative incidence of chronic lung allograft rejection ( P = 0.160) and the development of chronic kidney disease ( P = 0.757) were not significant between groups. Conclusions: The initiation of CRRT posttransplant may be a useful strategy to preserve cardiac and optimize volume management among critically ill patients.